1976
DOI: 10.1097/00000658-197607000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Gastrin Release and Gastric Secretion by Gastric Inhibitory Polypeptide (GIP) and Vasoactive Intestinal Polypeptide (VIP)

Abstract: Five dogs prepared with Heidenhain pouches received infusions of saline, GIP and VIP before and after a standard meat meal. Blood samples were obtained under basal conditions and at subsequent intervals for measurement of gastrin, insulin, GIP and VIP by radioimmunoassay. GIP and VIP infusions had no effect on basal levels of gastrin. GIP and VIP (in common with secretin and glucagon) were found to suppress food-stimulated release of gastrin and gastrin-stimulated acid secretion from the Heidenhain pouch. Insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 16 publications
3
22
0
1
Order By: Relevance
“…Immediately after a meal, the pH was high (about 5) so that the enzymes secreted in large quantities could exert their coagulating activity. The pH thereafter decreased progressively towards values more favourable to the overall proteolytic activity of pepsin (Henschel, 1973 ;Roy and Stobo, 1975 Debas and Grossman, 1974 ;Desbuquois, 1978 ;Hacki, 1980 ;McLeay and Bell, 1981) ; others seem to have an inhibitory effect on the secretion of acid (secretin, somatostatin, vasoactive intestinal peptide and glucagon) and enzymes (somatostatin and VIP) (Villar, Fender and Rayford, 1976 ;Arnold and Lankish, 1980 ;Hacki, 1980 ;McLeay and Bell, 1981 The psychic stimuli associated with the morning meal (sight, hearing, smell, taste and ingestion) (Siebers, 1978), as well as the distension of the abomasum, act via the parasympathic nervous system or via histamin, leading to a rapid increase in the secretion of enzymes and electrolytes, if the preruminant calf behaves like a monogastric animal (Davenport, 1968) …”
Section: Methodsmentioning
confidence: 99%
“…Immediately after a meal, the pH was high (about 5) so that the enzymes secreted in large quantities could exert their coagulating activity. The pH thereafter decreased progressively towards values more favourable to the overall proteolytic activity of pepsin (Henschel, 1973 ;Roy and Stobo, 1975 Debas and Grossman, 1974 ;Desbuquois, 1978 ;Hacki, 1980 ;McLeay and Bell, 1981) ; others seem to have an inhibitory effect on the secretion of acid (secretin, somatostatin, vasoactive intestinal peptide and glucagon) and enzymes (somatostatin and VIP) (Villar, Fender and Rayford, 1976 ;Arnold and Lankish, 1980 ;Hacki, 1980 ;McLeay and Bell, 1981 The psychic stimuli associated with the morning meal (sight, hearing, smell, taste and ingestion) (Siebers, 1978), as well as the distension of the abomasum, act via the parasympathic nervous system or via histamin, leading to a rapid increase in the secretion of enzymes and electrolytes, if the preruminant calf behaves like a monogastric animal (Davenport, 1968) …”
Section: Methodsmentioning
confidence: 99%
“…Initially, it was considered an inhibitor of gastric acid secretion, 83,84 but later studies demonstrated glucose-dependent stimulation of insulin secretion by GIP, suggesting an incretin role. 85 In time, the term GIP became synonymous with glucose inhibitory polypeptide.…”
Section: Impact Of Bariatric Surgery On Bone Metabolismmentioning
confidence: 99%
“…Targets for the hormone include fundic cells of the stomach, where GIP has been shown to inhibit acid secretion (49), and ␤-cells of the pancreatic islets, where GIP potentiates insulin release (15,39). Because of its insulin-releasing properties, GIP has been designated a physiological incretin, the proposed substance that mediates the enteroinsular axis and appears to play an important role in the maintenance of glucose homeostasis.…”
mentioning
confidence: 99%